Relationship between high normal TSH levels and metabolic syndrome components in type 2 diabetic subjects with euthyroidism - Lilit Petrosyan (Journal of Clinical & Translational Endocrinology, 2015)
Objective: Thyroid hormones as modulators of adaptive thermogenesis can potentially contribute to development of obesity. The purpose of our study is to observe a relationship between TSH and BMI, blood lipids, BP and HbA1c in type 2 diabetic subjects with euthyroidism. Methods: A total of 120 subjects with type 2 diabetes were recruited for this study from November 2012 to June 2014. Subjects were included in the study with TSH values between 0.4 and 4.5 mU/l, who did not take any thyroid medication and had a similar iodine diet. Subjects were weighed and anthropometric indices, lipid parameters, fasting plasma glucose, HbA1c, eGFR, blood pressure (BP) were documented. TSH was measured by an electrochemiluminescence immunoassay. Statistical analysis was performed by using SPSS 18(P value <0.05 was considered significant). Results: The mean age of the participants was 60.6 ± 11.6 years with a BMI of 25.3 ± 3.1 kg/m2. Serum TSH levels were significantly and positively associated with BMI, systolic and diastolic BP, serum triglyceride and HbA1c levels, whereas negatively with eGFR. Subjects with a TSH in a higher normal range (2.5–4.5 mU/I, n = 58) had a significantly higher BMI (26.7 ± 3 vs. 24.1 ± 2.7) and this relation remained significant adjusted for age and sex (P < 0.001). When TSH was in low normal range, the number of patients with glycemic goal (HbA1c > 7%) decreased from 27.5% to 12.5% (P = 0.02, adjusted for age and sex). Conclusion: In type 2 diabetic subjects with biochemical euthyroidism we found significant association between high normal TSH levels and components of metabolic syndrome. High normal TSH levels were associated with more number of subjects with glycemic goal (HbA1c >7%).